An Alternative Assessment Model to Improve a Translated Text from Indonesian into English - Tanuwijaya, Marwan; Nugroho, Aditya Cahyo; Ahdi, Pratama; Dewi, Novita (Indonesian Journal of English Language Studies (IJELS), 2016)
The main aspect of translation is how one’s expression in one language is replacedwith an equivalent representation in another language. The representation should beequivalent in terms of its stylistic, referential, and linguistic features. Whether there is a needfor a translation text to be classified as "weak," "fair" or "good," its acceptability and themeans of determining it as well as how to improve one’s translation quality were what weinvestigated in this article. National and international translation standards now exist, butthere are no generally accepted objective criteria for evaluating the quality oftranslation. Therefore, such an assessment is needed to reveal the quality of the translation ofa text from Indonesian into English. This article aimed to assess it using an alternativeinstrument and suggestions on how to improve translation quality which the authors adaptedfrom NAATI (National Accreditation Authority of Translators and Interpreters). Theyadopted the stylistic, referential, and linguistic components of NAATI’s translation qualityassessment. Based on the limited data that they had, a number of improvement procedureswere recommended. Keywords: assessment, text, translation quality and improvement